Development of a Trivalent Construct Omp18/AhpC/FlgH Multi Epitope Peptide Vaccine Against Campylobacter jejuni - Lou, Hongqiang; Li, Xusheng; Sheng, Xiusheng; Fang, Shuiqin; Wan, Shaoye; Sun, Aihua; Chen, Haohao (Frontiers in Microbiology, 2022)
Campylobacter jejuni (C. jejuni) is one of the major pathogens contributing to the enteritis in humans. Infection can lead to numerous complications, including but not limited to Guillain-Barre syndrome, reactive arthritis and Reiter’s syndrome. Over the past two decades, joint efforts have been made towards developing a proper strategy of limiting the transmission of C. jejuni to humans. Nevertheless, except for biosecurity measures, no available vaccine has been developed so far. Judging from the research findings, Omp18, AhpC outer membrane protein and FlgH flagellin subunits of C. jejuni could be adopted as surface protein antigens of C. jejuni for screening dominant epitope thanks to their strong antigenicity, expression of varying strains and conservative sequence. In this study, bioinformatics technology was adopted to analyze the T-B antigenic epitopes of Omp18, AhpC and FlgH in C. jejuni strain NCTC11168. Both ELISA and Western Blot methods were adopted to screen the dominant T-B combined epitope. GGS (GGCGGTAGC) sequence was adopted to connect the dominant T-B combined epitope peptides and to construct the prokaryotic expression system of tandem repeats of antigenic epitope peptides. The mouse infection model was adopted to assess the immunoprotective effect imposed by the trivalent T-B combined with antigen epitope peptide based on Omp18/AhpC/FlgH. In this study, a tandem epitope AhpC-2/Omp18-1/FlgH-1 was developed, which was composed of three epitopes and could effectively enhance the stability and antigenicity of the epitope while preserving its structure. The immunization of BALB/c mice with a tandem epitope could induce protective immunity accompanied by the generation of IgG2a antibody response through the in vitro synthesis of IFN-γ cytokines. Judging from the results of immune protection experiments, the colonization of C. jejuni declined to a significant extent, and it was expected that AhpC-2/Omp18-1/FlgH-1 could be adopted as a candidate antigen for genetic engineering vaccine of C. jejuni MAP.